TECHNOLOGIES FOR DEVELOPING INTERCULTURAL COMPETENCE OF FUTURE FOREIGN LANGUAGE TEACHERS THROUGH READING LITERARY WORKS (ON THE EXAMPLE OF METHODS OF READING THE WORK OF IMMIGRANT-MUSLIM WRITERS IN THE USA) - Sayyora Rustamjon kizi, Mirzaeva (Journal of Higher Education and Academic Advancement, 2025)
Objective: This study explores innovative technologies and instructional strategies to develop intercultural competence in future foreign language teachers through the analysis of literary works by U.S.-based immigrant-Muslim authors. Method: The research employs digital annotation platforms, interactive reading journals, and reflective activities to engage students with themes of identity, marginalization, and hybridity within culturally complex texts. These strategies integrate literary analysis with intercultural pedagogy to promote critical thinking and empathy. Results: The findings indicate that using immigrant-Muslim literature enhances sociolinguistic sensitivity and intercultural understanding, equipping students with the cultural sensitivity and ethical awareness necessary for inclusive teaching. These texts served as cultural documents, fostering a deeper understanding of marginalized perspectives. Novelty: This article proposes a novel, technology-supported pedagogical framework that links reading strategies with intercultural reflection, emphasizing marginalized voices often excluded from mainstream curricula. It offers a new approach to teacher training by incorporating minority-authored literature and digital tools, filling a gap in existing educational methodologies. .